The Burden of Neonatal Diseases Attributable to Ambient PM 2.5 in China From 1990 to 2019 - Yuan, Jia; Shi, Lu; Li, Hongbo; Zhou, Jing; Zeng, Lingxia; Cheng, Yue; Han, Bei (Frontiers in Environmental Science, 2022)
BACKGROUND Air pollution exposure is an environmental risk to public health. And the available data on relationships of air pollution and neonatal disease burden are scarce. This study assessed neonatal disease burden attributable to Particulate Matter 2.5 (PM 2.5) pollution in China. METHODS Data of PM 2.5 pollution exposure levels and neonatal disease burden attributable to PM 2.5 in China from 1990-2019 were obtained from the Global Burden of Disease Study 2019 (GBD2019); Data of PM2.5 concentration was collected from the Bulletin of the State of the Ecological Environment in China; Data of perinatal mortality was collected from the Chinese Maternal and Child Health Surveillance Network. Deaths, Disability-adjusted life years (DALYs), Year of life lost (YLLs), and Years lived with disability (YLDs) are primary indicators used to assess neonatal diseases burden. The correlation of PM2.5 pollution and neonatal death was analyzed. Average Annual Percentage Change (AAPC) and increment were used to assess exposure levels and disease burden trends. RESULTS PM 2.5 pollution exposure level of newborns in China is much higher than global average, 32.08 per 100 people (95% UI: 26.57-38.06) in 2019 compared to 1990 (15.86 per 100 people, 95% UI: 6.83-30.88), with an increase of 102.27%. And it is statistically verified PM2.5 concentration was positively correlated with neonatal disease deaths (r=0.9534, P=0.0009) and DALYs (r=0.9534, P=0.0009). The overall disease burden of neonatal diseases attributed to PM 2.5 pollution in China has decreased from 1990 to 2019, with a decrement of 5738.34 deaths (decreased: 56.85%), 51.01 person/years (decreased: 56.84%) for DALYs, 51.23 person/years (decreased: 57.11%) for YLLs and an increase of 150.69 person/years (increased: 31.71%) for YLDs. CONCLUSIONS There exists positive correlation between environmental pollution and neonatal diseases in China. The number of neonatal disease deaths, DALYs, and YLLs due to PM 2.5 pollution showed a decreasing trend with the environmental pollution control. For the rising YLDs, there is a need to improve survival rates while focusing on prognosis of neonatal disease and reducing the burden of disease brought on by disability. Controlling environmental pollution is likely to help reduce neonatal disease burden, especially premature birth and neonatal encephalopathy.